Does gastric acid release plasma somatostatin in man?. Issue 11 (November 1984) - Lucey, M R; Wass, J A; Fairclough, P D; O'Hare, M; Kwasowski, P; Penman, E; Webb, J; Rees, L H
Abstract : Food and insulin hypoglycaemia raise plasma concentrations of somatostatin. Both also stimulate gastric acid secretion but it is not clear whether gastric acid itself has any effect on somatostatin secretion. We, therefore, studied the effect on plasma concentrations of somatostatin of infusion of 0.1 N HC1 into the stomach and duodenum of healthy subjects. Plasma somatostatin did not rise with a small dose of HC1 given intragastrically (15 mmol) or intraduodenally (4 mmol). After an intraduodenal infusion of 60 mmol HC1 over 30 minutes, sufficient to reduce intraluminal pH to 2, plasma somatostatin rose moderately in five subjects from a mean value (+/- SEM) of 32 +/- 3 pg/ml to a peak at 10 minutes of 54 +/- 11 pg/ml. It is concluded that: (a) intragastric acid infusions do not release circulating somatostatin in man; and (b) that intraduodenal acidification albeit at grossly supraphysiological doses is a moderate stimulus of plasma somatostatin release. Therefore, gastric acid is unlikely to be a major factor mediating postprandial plasma somatostatin release in man.